A novel key management protocol for vehicular cloud security - Nayana Hegde; Sunilkumar S. Manvi (Universitas Ahmad Dahlan, 2019)
Vehicular cloud computing (VCC) is a new hybrid technology which has become an outstanding area of research. VCC combines salient features of cloud computing and wireless communication technology to help drivers in network connectivity, storage space availability and applications. VCC is formed by dynamic cloud formation by moving vehicles. Security plays an important role in VCC communication. Key management is one of the important tasks for security of VCC. This paper proposes a novel key management protocol for VCC security. Proposed scheme is based on Elliptical Curve Cryptography (ECC). The simulation results demonstrated that the proposed protocol is efficient compared to existing key management algorithms in terms of key generation time, memory usage and cpu utilization.